2015
DOI: 10.1371/journal.pone.0141663
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Mechanisms of Cortical Enhancement Induced by the Repetitive Pairing of Visual/Cholinergic Stimulation

Abstract: Repetitive visual training paired with electrical activation of cholinergic projections to the primary visual cortex (V1) induces long-term enhancement of cortical processing in response to the visual training stimulus. To better determine the receptor subtypes mediating this effect the selective pharmacological blockade of V1 nicotinic (nAChR), M1 and M2 muscarinic (mAChR) or GABAergic A (GABAAR) receptors was performed during the training session and visual evoked potentials (VEPs) were recorded before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Progress is hampered by lack of appropriate models of associative and passive learning in developing and adult experimental animals, respectively. Passive learning in adult animals has been reported (Cooke and Bear, 2010), but some forms also require cholinergic signaling (Gavornik and Bear, 2014;Kang et al, 2015). On the other hand, plasticity during vocal learning in juvenile birds may require inputs from the frontal areas, suggesting that top-down modulation can occur before the critical periods close (Puzerey et al, 2018).…”
Section: Continuity Of Plasticity During Cortical Maturationmentioning
confidence: 99%
“…Progress is hampered by lack of appropriate models of associative and passive learning in developing and adult experimental animals, respectively. Passive learning in adult animals has been reported (Cooke and Bear, 2010), but some forms also require cholinergic signaling (Gavornik and Bear, 2014;Kang et al, 2015). On the other hand, plasticity during vocal learning in juvenile birds may require inputs from the frontal areas, suggesting that top-down modulation can occur before the critical periods close (Puzerey et al, 2018).…”
Section: Continuity Of Plasticity During Cortical Maturationmentioning
confidence: 99%
“…This also reduced the extent of spatial integration, evident by a shift of a neuron’s preferred length toward shorter bars and a concomitant decrease in its spatial summation area (Roberts et al, 2005). Activation of cholinergic receptors also causes long-term enhancement of the magnitude of visual evoked potentials (Kang and Vaucher, 2009; Kang et al, 2015) and the behavioral sensitivity to specific visual orientations (Kang et al, 2014). Manipulations of cholinergic input also influence attentional modulation in visual cortex.…”
Section: Overview Of Cholinergic Functionmentioning
confidence: 99%
“…Changes in the relative balance of thalamic input and synaptic feedback could underlie the fact that knockout of specific muscarinic receptors reduces contrast sensitivity and frequency selectivity in V1 as well as altering receptive field size (Groleau et al, 2014; Groleau et al, 2015). Cholinergic modulation has also been shown to cause long-term enhancement of visual evoked potential and behavioural sensitivity (Kang and Vaucher, 2009; Kang et al, 2014; Kang et al, 2015) that could be relevant to the coding of visual cues for spatial location.…”
Section: Cholinergic Modulation Of Cortical Circuit Propertiesmentioning
confidence: 99%
“…Subsequent studies have shown that co-application of ACh or muscarinic agonists with glutamate can induce a prolonged increase in response to glutamate in somatosensory cortical neurons (Lin and Phillis, 1991; Metherate et al, 1987). When the application of ACh or electrical stimulation of BF is paired with sensory stimulation in the somatosensory (Donoghue and Carroll, 1987; Howard III and Simons, 1994; Lamour et al, 1988; Metherate et al, 1987; Rasmusson and Dykes, 1988; Tremblay et al, 1990a, b), auditory cortex (Bakin and Weinberger, 1996; Dimyan and Weinberger, 1999; Edeline et al, 1994; Kilgard and Merzenich, 1998a, b; Kilgard et al, 2001), and visual cortex (Kang et al, 2014a; Kang et al, 2015), prolonged enhanced responses to the paired sensory stimuli are observed, often along with changes in behavior (Kang et al, 2014b). These studies have also revealed that cholinergic antagonists cannot reverse the prolonged changes, thereby confirming that the induction but not maintenance of prolonged changes requires ACh (Lamour et al, 1988).…”
Section: Plasticitymentioning
confidence: 99%